Relationship between asymptomatic rotavirus infection and jaundice in neonates: a retrospective study - Nu Ri Hwang; Jin Kyu Kim (BMC, 2018)
Abstract Background Rotavirus (RV) infection in neonates can be mild or even asymptomatic. In RV infection, jaundice is often reported, but the relationship between jaundice and RV infection has not been studied. This study aimed to determine the importance of asymptomatic RV screening in neonates with jaundice. Methods Neonates from the neonatal intensive care unit (NICU) of Chonbuk National University Hospital, those transferred from local obstetrics and gynecology hospitals and outpatient clinics were selected from 2014 to 2017. The study included only infants aged between 3 and 28 days. Jaundice was defined according to gestational age and birth age, in accordance with the American Academy of Pediatrics guidelines criteria. RV infection was confirmed by a stool test, and RV screening and laboratory tests were performed at admission. Results Among 596 patients, 166 patients had jaundice. RV infection was observed in 70 (42%) jaundice patients. There were 36 (22%) jaundice patients with asymptomatic RV infection. Patients with onset of jaundice 3-7 days after birth had a high incidence of RV infection. When the RV test was positive, the risk of jaundice was significantly high [odds ratio (OR) 1.89; 95% confidence interval (CI), 1.20-2.98; p = 0.006]. Conclusions Infants with the onset of jaundice > 3 days after birth were likely to have RV infection. Therefore, we suggest that screening tests for RV infection be included as part of the evaluation of jaundiced infants presenting to NICU.